The relationship between Taekwondo training habits and injury: a survey of a collegiate Taekwondo population - Covarrubias N; Bhatia S; Campos LF; Nguyen DV; Chang EY (Dove Medical Press, 2015)
Natalia Covarrubias,1 Subir Bhatia,2 Luis F Campos,3 Dahn V Nguyen,2,3 Eric Y Chang1,4,51Department of Physical Medicine and Rehabilitation, University of California Irvine, Irvine, CA, USA; 2School of Medicine, University of California Irvine, Irvine, CA, USA; 3Institute for Clinical and Translational Science, Irvine, CA, USA; 4Department of Anesthesiology and Perioperative Care, University of California Irvine, Irvine, CA, USA; 5Reeve-Irvine Research Center, Irvine, CA, USA Objective: To correlate training habits of Taekwondo (TKD) athletes to risk for injury. Background: TKD is a Korean marital art that has been growing in popularity, with nearly 2 million individuals practicing the sport in the United States. Because of the combative nature of the sport, injuries are an inherent risk. However, data on proper training habits, types of injuries sustained during training, and recommendations for athletes to avoid injury are lacking. Frequently, studies of TKD evaluate athletes’ injuries during tournaments, but most do not evaluate athletes in training. Hypothesis: Increased training would potentially create more injuries secondary to increased exposure. Methods: This is a cross-sectional observational survey of 72 collegiate TKD athletes from the Pacific West Sanctioned Taekwondo Tournaments in the 2008–2009 season. Variables analyzed during training and competitions were training sessions per week, workout habits, belt level, years of experience, and characteristics of injury (location, type, mechanism, situation, treatment, and days missed). Results: TKD training habits of individuals who practiced four or more times per week (odds ratio [OR], 4.5; P=0.005) or sparred for more than 2 hours (OR, 8.7; P=0.003) were associated with significantly increased odds (risk) of sustaining an injury. Those who had more than 3 years of tournament experience were more likely to sustain an injury (OR, 0.198; P=0.020). Conclusion: Increased risk for injury with more frequent practice and longer sparring should remind coaches and trainers that monitoring and adjusting the athletes’ training schedules and exposure time could decrease the chance of injury. An athlete that has spent more years in tournaments along with high-frequency and long-duration training was associated with greater risk for injuries. Prevention and education about the risk for exposure to injury may may help athletes and trainers promote prevention strategies and adjust an athletes’ training and tournament schedules to decrease the risk for injury. Keywords: sports injuries, martial arts, collegiate athletes, training injuries